A internet na evolução do pensamento folkcomunicacional - Corniani, Fabio Rodrigues (2009)
Since the beginning of research in folkcommunication, this area of ​​study has been continuously evolving with the discovery of new research objects in view of its rapid development. The Internet is changing the way people communicate and live. In the midst of these changes, Folkcommunication, which permeates mass communication because of its genesis in folklore, has been gaining new objects with the evolution of information technologies. The main question this paper raises is to see how the Internet has influenced the thinking of folkcommunication. However, this study aims to elucidate some questions such as: "Who are the new folkcommunication leaders?"; "How does the mass media influence the content of the folk message on the Internet?"; "Did the Internet folk message have to be adapted to the medium?" "" "Can we find demonstrations for all folk audiences on the Internet?", and "How do audiences receive the content of communication?" based on concepts by Luiz Beltrão, and updates on this by José Marques de Melo, Joseph Luyten, Cristina Schmidt, Osvaldo pattern close to the manifestations found in other supports even though temporal and spatial updates can be verified. (AU)